DOI: 10.18297/etd/393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slope and paver characteristics on performance of permeable pavement GI.

Abstract: DEDICATIONI dedicate my dissertation to my family and many friends. A special feeling of gratitude to my loving parents, whose words of encouragement and push got me this far. I also dedicate this dissertation to my wife, who stood by me, and I will always appreciate all her support throughout the process. This dissertation is an experimental study based on the findings of two Green Infrastructure (GI) stormwater control measures (SCMs) in Louisville, KY, which focused on the effects of the physical environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
(106 reference statements)
1
4
0
Order By: Relevance
“…However, the results showed that some of the WCRs located on the far east side of the pavement section received less runoff during this study. These results are similar to the finding of Ehsaei (2013) that conducted wetting and clogging front on a pavement section with underlying layers in a laboratory scale experiment. Another possibility for smaller recording of the far east sensors could be the deposition of the particles and debris from the earlier events, thus changing the runoff direction and hence the runoff did not infiltrate over these reflectometers during the following events.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the results showed that some of the WCRs located on the far east side of the pavement section received less runoff during this study. These results are similar to the finding of Ehsaei (2013) that conducted wetting and clogging front on a pavement section with underlying layers in a laboratory scale experiment. Another possibility for smaller recording of the far east sensors could be the deposition of the particles and debris from the earlier events, thus changing the runoff direction and hence the runoff did not infiltrate over these reflectometers during the following events.…”
Section: Discussionsupporting
confidence: 88%
“…Different aspects of clogging mechanisms have been conducted by earlier studies through laboratory experiments (Haselbach, 2010, Ehsaei, 2013, field investigations (Bean et al, 2007, Pezzaniti et al, 2009, Lucke and Beecham, 2011 and modelling (Deo et al, 2010). Haselbach (2010) investigated the effects of extreme events and runoff with high loads of clay on pervious concrete clogging, concluding that the clay particles accumulated on the upper layers of the pavement and surface sweeping followed by rinsing was an efficient way to return infiltration to an acceptable level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The joint spaces are likely to get clogged by debris with various particle sizes. Fine particles such as clayey material migrate through the gaps and create a seal at the bottom of storage gallery, obstructing the interface with native soils and jeopardizing the exfiltration capacity of the system, while larger (mostly organic) debris contribute to surface clogging (Ehsaei 2013) (Balades, Legret et al 1995). In order to investigate the gap size efficacy in clogging progression and consequently captured runoff capacity, three different paver block types are utilized to cover the permeable surface ( Figure 1).…”
Section: Laboratory Modelingmentioning
confidence: 99%
“…Measuring the infiltration rates is employed to demonstrate the clogging progression on the permeable surface. It has been found that clogging is concentrated at the upper edge of the pavement and is progressed over time from the upgradient edge (Ehsaei 2013). Sediment accumulation diminishes the infiltration rates, and conducting regular maintenances are necessary to restore the designated captured runoff volume by the PICPs (Al-Rubaei, Stenglein et al 2012).…”
Section: Introductionmentioning
confidence: 99%